Evaluasi Geometrik Jalan Ditinjau Dari Aspek Alinyemen Horisontal Terhadap Pelebaran Tikungan Jalan Bangsri - Kelet - Decky Rochmanto; Khotibul Umam; Fara Fitriatul Fauziah (Reviews in Civil Engineering, 2019)
The Bangsri - Kelet highway is a provincial road that has road geometric conditions (horizontal alignments and vertical alignments) which can endanger the safety of road users. Then the Bangsri-Kelet highway evaluation and study is needed to get a horizontal alignment and vertical alignment in accordance with Bina Marga standards. Using the observation survey method, using road geometric data and primary and secondary data The results of the analysis show that the Bangsri-Kelet road is included in the Collector's function with class II B. There are 7 horizontal alignments included in the Bina Marga standard and included in the SCS bend type ( Spiral-Circle-Spiral). With PPV in the form of 105 pieces consisting of 52 concave arch PPV and 53 convex curved PPV.